2021
DOI: 10.21037/qims-20-1314
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the predictive accuracy of lung cancer, metastases, and benign lesions using an artificial intelligence-driven computer aided diagnosis system

Abstract: Background: Artificial intelligence (AI) products have been widely used for the clinical detection of primary lung tumors. However, their performance and accuracy in risk prediction for metastases or benign lesions remain underexplored. This study evaluated the accuracy of an AI-driven commercial computer-aided detection (CAD) product (InferRead CT Lung Research, ICLR) in malignancy risk prediction using a realworld database.Methods: This retrospective study assessed 486 consecutive resected lung lesions, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Interestingly, their model was comparable to radiologists in the evaluation of prior and recent CT images, but it outperformed the radiologists when evaluating recent CT image only. Li et al [ 163 ] evaluated the diagnostic performance of a CAD commercial software program called InferRead CT Lung Research (ICLR) which was based on 3D CNN. They found that ICLR had high accuracy in risk prediction of bronchogenic carcinoma unlike benign or metastatic lesions.…”
Section: Nodule Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, their model was comparable to radiologists in the evaluation of prior and recent CT images, but it outperformed the radiologists when evaluating recent CT image only. Li et al [ 163 ] evaluated the diagnostic performance of a CAD commercial software program called InferRead CT Lung Research (ICLR) which was based on 3D CNN. They found that ICLR had high accuracy in risk prediction of bronchogenic carcinoma unlike benign or metastatic lesions.…”
Section: Nodule Classificationmentioning
confidence: 99%
“…Regarding the diagnostic performance, a bunch of studies proved that deep leaning is superior to ML models, owing to self-learning capabilities of the later [ 78 , 149 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 , 173 , 174 , 175 ]. Song et al [ 176 ] compared three types of neural networks; convolutional neural network, deep neural network, and stacked autoencoder (SAE).…”
Section: Nodule Classificationmentioning
confidence: 99%
“…In [9], the Nonparallel Plane Proximal Classifier (NPPC) become stated for cancer type in a Computer-Aided Diagnosis (CAD) system to assure excessive type accuracy and to minimize the computation time. Artificial intelligence-primarily based computer diagnostics (CAD) is a non-invasive, goal-oriented solution that facilitates radiologists' diagnosis of lung nodules [10]. However, Valvular coronary heart problems had been one of the toughest elegance troubles.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this paper [9], the Nonparallel Plane Proximal Classifier (NPPC) become stated for cancer type in a Computer-Aided Diagnosis (CAD) system to assure excessive type accuracy and to minimize the computation time. Artificial intelligence-primarily based totally computer diagnostics (CAD) is a non-invasive, goal-oriented solution that facilitates radiologists' diagnosis of lung nodules [10]. However, Valvular coronary heart problems had been considered to be one of the toughest elegance troubles.…”
Section: Literature Reviewmentioning
confidence: 99%